Business Model Community Based Marketing For Beras Sagu, PERSADIA Community - AZMIA, NORA; Evy Pramita Hidariyani; Widhi Ariyo Bimo (Moneter: Jurnal Keuangan dan Perbankan, 2023)
Indonesia was ranked 6th among 10 countries with the highest number of people with diabetes mellitus, which amounted to 10.3 millions (International Diabetes Federation, 2017). The causes mostly are diet (eating habits) and lifestyle. The staple food of the Indonesian people is still dominated by rice which comes from the rice plant and has a high glycemic index which contribute to high glucose levels in the body. PUSPIPTEK BPPT (Science and Technology Research Center BPPT) developed Sago Rice® namely rice made from sago starch (Metroxylon spp). Sago Rice® was created with the aim of providing an alternative carbohydrate food to replace rice. The product has clinical trial results with a low glycemic index compared to other types of rice. A special marketing strategy is needed to introduce Sago Rice® to wider community in Indonesia. This article is an elaboration of marketing aspect from a thesis project conducted in 2016 – 2017. The research aimed to initiate a marketing strategy for Sago Rice® product. Qualitative descriptive research method was used to make a community-based marketing strategy through the PERSADIA Community (Indonesian Diabetes Association). The results showed that the community-based marketing strategy was well received by the community members. In addition to providing value-added knowledge of alternative carbohydrate sources, this strategy also improves public health. Thus, a community-based marketing strategy can be used as one of the marketing strategies for Sago Rice® in Indonesia.